Marine Science: An Illustrated Guide to Science - Diagram Group (Chelsea House Publications, 2012)
Each volume offers full-color diagrams, graphs, charts, and maps on every page that illustrate the essential elements of the subject, while parallel text provides key definitions and step-by-step explanations Each volume offers full-color diagrams, graphs, charts, and maps on every page that illustrate the essential elements of the subject, while parallel text provides key definitions and step-by-step explanations